2008
DOI: 10.2746/042516408x320889
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound‐guided aspiration of unilateral twin gestation in the mare

Abstract: Embryo reduction of unilateral twin vesicles is normally successful before fixation of the vesicles. After fixation, however, it becomes a challenge, and the later in the gestation period that the reduction is performed, the greater the challenge. One therapy to reduce a twin into a singleton pregnancy is the transvaginal ultrasound-guided aspiration (TUGA) of one of the vesicles. The results of 35 unilateral twin reductions by TUGA are discussed in this paper and possible negative influences of age, parity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 9 publications
3
18
1
1
Order By: Relevance
“…Nevertheless, at least for the 2-3 month losses a delayed effect of TUGR is a plausible contributory factor. In the case of transabdominal ultrasound-guided twin reductions, it is accepted that the placenta of the surviving twin is never able to regain the endometrial attachment area 'lost' to its cotwin, leading to an increased risk of placental insufficiency later in gestation that can result in abortion or the birth of a emaciated foal [12,13] despite mummification of its twin; placental insufficiency following TUGR has not been reported, but could conceivably be an issue if The likelihood of success in the current study was not significantly influenced by the technique used for TUGR, which is in agreement with the observations of Govaere et al [5] for mares with unilateral twins. One of the biggest risks of performing allantoic/yolk-sac fluid aspiration in unilateral twins is damage to the developing membranes or to the chorioallantoic-endometrial attachment of the co-twin as a result of puncture, accidental aspiration, leakage of fluid and/or collapse of the manipulated vesicle [1].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Nevertheless, at least for the 2-3 month losses a delayed effect of TUGR is a plausible contributory factor. In the case of transabdominal ultrasound-guided twin reductions, it is accepted that the placenta of the surviving twin is never able to regain the endometrial attachment area 'lost' to its cotwin, leading to an increased risk of placental insufficiency later in gestation that can result in abortion or the birth of a emaciated foal [12,13] despite mummification of its twin; placental insufficiency following TUGR has not been reported, but could conceivably be an issue if The likelihood of success in the current study was not significantly influenced by the technique used for TUGR, which is in agreement with the observations of Govaere et al [5] for mares with unilateral twins. One of the biggest risks of performing allantoic/yolk-sac fluid aspiration in unilateral twins is damage to the developing membranes or to the chorioallantoic-endometrial attachment of the co-twin as a result of puncture, accidental aspiration, leakage of fluid and/or collapse of the manipulated vesicle [1].…”
Section: Discussionsupporting
confidence: 90%
“…Other studies reported higher success rates (46-51%) based on an examination performed 7-10 days after the TUGR procedure [3,5].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In den letzten Jahren wurde von verschiedenen Autoren die transvaginale ultrasonographisch-geleitete Aspiration (TUA) zur Reduktion unicornualer und bicornualer Zwillingsgraviditäten im fortgeschrittenen Trächtigkeitsstadium beschrieben (Bracher et al 1993, Jonker et al 1995, Morris et al 1999, MacPherson and Reimers 2000, Mari et al 2004, Becker et al 2006, Govaere et al 2008. Die am Vorhandensein eines vitalen Embryos 5-14 Tage nach der Zwillingsreduktion oder anhand von Abfohldaten ermittelten Erfolgsraten variierten in diesen Studien deutlich (9-75 %), wobei ein Einfluss der Lokalisation (Bracher et al 1993), des Trächtigkeitstages (Jonker et al 1995, Mari et al 2004, Becker et al 2006) und der Applikation eines nichtsteroidalen Antiphlogistikums (Becker et al 2006) …”
Section: Zusammenfassungunclassified